Semantic Segmentation Using Convolutional Neural Networks for Volume Estimation of Native Potatoes at High Speed - Chasquibol Silva, Nancy Ascención (2023)
Sacha inchi (Plukenetia huayllabambana) oil was co-microencapsulated with natural antioxidant extracts (NAE), such as camu-camu (Myrciaria dubia (HBK) Mc Vaugh) fruit, Añil variety Andean potato (Solanum tuberosum andigenum, and elderberry fruit (Sambucus peruviana). Gum Arabic and the ternary combination of gum Arabic (GA) + maltodextrin (MD) + whey protein isolate (WPI) at different formulations were used as coating materials for the encapsulation process using spray-drying. The moisture content, particle size distribution and morphology, total phenolic content, antioxidant activity, fatty acid and sterol composition, oxidative stability, and shelf-life were evaluated. Co-microcapsules of sacha inchi (P. huayllabambana) oil with camu camu skin extract (CCSE) at 200 ppm encapsulated with GA + MD + WPI had the highest total polyphenol content (4239.80 µg GAE/g powder), antioxidant activity (12,454.00 µg trolox/g powder), omega-3 content (56.03%), ß-sitosterol (62.5%), greater oxidative stability (Oxidation Onset temperature of 189 °C), higher shelf-life (3116 h), and smaller particle sizes (6.42 µm). This research enhances the knowledge to obtain microcapsules containing sacha inchi (P. huayllabambana) oil with natural antioxidant extracts that could be used for the development of functional foods. Further research is needed to study the potential interactions and their influence between the bioactive components of the microcapsules and the challenges that may occur during scale-up to industrial production.